SOSIALISASI PROGRAM KARTU INDONESIA PINTAR KULIAH DI DESA PAKISJAJAR KABUPATEN MALANG - Lis Susilawati; Rina Wijayanti; Nurwakhid Muliyono; Chindy Hanggara Rosa Indah (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2023)
The socialization of the Indonesia Smart College Card is one of the government's programs to facilitate and assist lower-middle class people about the benefits of the Indonesia Smart College Card for students who will continue on to tertiary institutions by taking advantage of the Indonesia Smart College Card scholarship to help pay for Study Fees at tertiary institutions.